Association of dyslipidemia with chronic non-malignant pain in elderly patients with femoral neck fractures treated by primary total hip arthroplasty: a retrospective study. Issue 9 (September 2021) - Wang, Chen; Xu, Bo; Wang, Pengfei; Yu, Weiguang; Zeng, Xianshang; Xiong, Nana; Yin, Pingping; Liu, Qilong; Lin, Huanyi
Objective: The association of chronic non-malignant pain (CNP) with dyslipidemia is unclear. This retrospective study was performed to evaluate the association between CNP and dyslipidemia in elderly patients with femoral neck fractures (FNFs) treated by primary unilateral total hip arthroplasty (THA). Methods: We retrospectively identified 521 consecutive patients with FNFs (AO/OTA type 31B) who underwent primary unilateral THA from 2009 to 2021. The study population was divided into patients with and without CNP. Serum lipids were measured for each patient. The association between CNP and dyslipidemia was assessed using a multivariate binary logistic regression model. Results: In total, 436 patients (220 with CNP, 216 without CNP) were eligible for analysis. In the quantile regression, the adverse effect of CNP was significantly attenuated by resilience in patients with a high high-density lipoprotein (HDL) concentration and low low-density lipoprotein (LDL) concentration. The multivariate binary logistic regression model showed that the HDL and LDL concentrations were the only variables significantly associated with the development of CNP. Conclusion: Both a low HDL and high LDL concentration may result in the occurrence of CNP in elderly patients with FNFs treated by primary unilateral THA.